Analisis Spasial Kebutuhan Tempat Pembuangan Sampah Sementara Di Kota Kendari - Laode Naufal Zayyan Anbiya; Laode Muhammad Iradat Salihin; Fitra Saleh; Nurgiantoro Nurgiantoro (JAGAT (Jurnal Geografi Aplikasi dan Teknologi), 2024)
Growth rapid population causing volumes of daily waste in Kendari City to increases, reasons that need Temporary Disposal Sites (TPS) need to be noticed. Image data is used to obtain information on land use in determining TPS land physique suitability. This study was conducted in the District of Wua-wua because it owns the most densely populated settlement in Kendari City. This study aims to : (1) Determine Temporary TPS land physique suitability using Sentinel imagery and Google Earth Images; and (2) Determine a new location for Temporary TPS. The sample was determined based on houses, including house size 10 houses, 40 houses, and big houses size 50 houses. Parameters used in determining suitability physique TPS land is the distance from settlement, road, and river. Data was analyzed using the Normalized Difference Built-Up Index (NDBI) to obtain index density buildings and overlays for suitability physique land and quantity Temporary TPS needs. Research results namely : (1) There are three suitable Temporary TPS land that is No in accordance covering an area of 486 ha, enough suit 308 ha and very corresponds to 107 ha; (2) Need for TPS in the District Wua-wua that is 55 units and spread throughout Subdistrict Wua-Wua Kendari City.